Neonatal progeriod syndrome associated with biallelic truncating variants in POLR3A. Issue 12 (9th September 2016) - Jay, Allison M.; Conway, Robert L.; Thiffault, Isabelle; Saunders, Carol; Farrow, Emily; Adams, John; Toriello, Helga V.
Abstract : Wiedemann–Rautenstrauch syndrome, also known as neonatal progeroid syndrome, is a rare condition with fewer than 40 patients reported in the literature. Characteristic physical findings include neonatal progeroid appearance, sparse scalp hair, prominent scalp veins, and lipoatrophy; in addition, neonatal teeth are often a distinctive finding. The inheritance pattern of this disorder has been postulated to be autosomal recessive, although a specific gene has not been identified. Here we report an infant with the characteristic phenotypic features of Wiedemann–Rautenstrauch syndrome in whom exome sequencing identified two pathogenic variants in POLR3A : c.1909+18G>A; p.(Y637Cfs*23) and c.2617C>T; p.(R873*). Mutations in POLR3A (OMIM #614258) are associated with 4H leukodystrophy syndrome characterized by the triad of hypomyelination, hypodontia, and hypogonadotrophic hypogonadism. The present patient's genotype implies a broader phenotypic range for POLR3A mutations and might expand the clinical spectrum. This proband is notable because she had two null pathogenic variants. Replication in other patients clinically diagnosed with Wiedemann–Rautenstrauch syndrome is needed to further demonstrate this gene‐disease association. © 2016 Wiley Periodicals, Inc.